Cut in stone: Confederate monuments and theological disruption - Newson, Ryan Andrew (Baylor University Press, 2020)
"Theological analysis of the meaning of Confederate monuments, arguing for their recontextualization through a counternarrative about whiteness, memory, and the goal of humanity"--